Livelihood strategies of resource poor farmers in strigainfested areas of western Kenya - Manyong, Victor M.; Alene, A.; Odhiambo, G.D.; Mignouna, Hodeba D.; Bokanga, M.; Omanya, G.; Nindi, S.J. (2007)
Striga hermonthica (del) Benth is threatening rural livelihoods in western Kenya where maize is the major food and cash crop. Vulnerability analysis was conducted on a sample of 802 households in eight districts of Nyanza and Western provinces. Farmers perceived Striga as the major cause of poverty and food insecurity. Both household income and child nutrition indicators showed alarming conditions for the majority of households. The coping strategies and informal safety nets were not capable of addressing the vulnerability issue successfully. A logistic regression model of determinants of poverty was estimated to examine the determinants and correlates of poverty. Results revealed certain characteristics of households that were more likely to be poor: poor access to land and farm assets; high dependency ratio; headed by older farmer with low education attainment; no off-farm work, no cash crops; depend on credit; Striga has been on the farm for long, high perceived yield loss to Striga given high dependency on maize for livelihoods; adopt no integrated Striga control options; and live in Bondo and Vihiga districts. The paper concludes with implications for policy to improve the livelihoods of small-scale farmers in the Striga-affected areas of western Kenya.